Dialektika Ulama dalam Menganalisis Konsep Ketuhanan: Studi atas Pengalaman Subjektif dalam Ilmu Kalam: The Dialectic of Scholars in Analyzing the Concept of Divinity: A Study of Subjective Experience in theology - Surni Kadir (Fakultas Agama Islam, Universitas Muhammadiyah Palu, 2026)
Konsep ketuhanan dalam Islam telah menjadi objek perdebatan panjang di kalangan ulama, terutama dalam disiplin Ilmu Kalam. Dialektika pemikiran ulama mencerminkan dinamika epistemologi Islam yang berkembang dari era klasik hingga kontemporer. Studi ini bertujuan untuk menganalisis pengalaman subjektif ulama dalam memahami konsep ketuhanan melalui pendekatan historis dan fenomenologis. Penelitian ini menggunakan metode kualitatif dengan studi kepustakaan terhadap karya-karya mutakallimun dari berbagai mazhab, termasuk Asy‘ariyah, Maturidiyah, dan Mu‘tazilah. Hasil penelitian menunjukkan bahwa pengalaman subjektif ulama dipengaruhi oleh latar belakang sosial, intelektual, serta respons terhadap tantangan filosofis dan teologis pada masanya. Perbedaan metodologi dalam menafsirkan sifat-sifat Tuhan menegaskan adanya pluralitas dalam tradisi pemikiran Islam tanpa menghilangkan esensi tauhid. Studi ini memberikan kontribusi bagi penguatan wacana keislaman berbasis argumentasi rasional dan dialogis, serta relevan dalam menjawab tantangan kontemporer dalam pemahaman ketuhanan. The concept of divinity in Islam has been the object of long debate among Islamic scholars, especially in the discipline of Kalam (Theology). The dialectic of Islamic thought reflects the dynamics of Islamic epistemology that developed from the classical to the contemporary era. This study aims to analyze the subjective experiences of Islamic scholars in understanding the concept of divinity through a historical and phenomenological approach. This research uses a qualitative method with a literature review of the works of mutakallimun from various schools of thought, including the Ash'ariyah, Maturidiyah, and Mu'tazilah. The results show that the subjective experiences of Islamic scholars are influenced by their social and intellectual backgrounds, as well as responses to the philosophical and theological challenges of their time. Differences in methodology in interpreting the attributes of God emphasize the existence of plurality in the tradition of Islamic thought without eliminating the essence of monotheism. This study contributes to strengthening Islamic discourse based on rational and dialogical arguments, and is relevant in addressing contemporary challenges in understanding divinity.